2015
DOI: 10.1016/j.abb.2014.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Design and characterization of a photo-activatable hedgehog probe that mimics the natural lipidated form

Abstract: We have generated a photoactivatable form of sonic hedgehog protein by modifying the N-terminal cysteine with the heterobifunctional photocrosslinker 4-maleimidobenzophenone (Bzm). The Bzm modification on ShhN imparted a significant increase in activity as assessed in the C3H10T1/2 functional assay with potency comparable to that of the endogenous dual-lipidated form of ShhN (ShhNp). Reversed-phase HPLC analysis indicated that the increase in activity compared to unmodified ShhN may be due in part to the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…A number of small molecules that act at the level of the GLI transcription factors have been identified with varying mechanisms and understanding of action and so we assembled a GLI antagonist panel consisting of GANT58 and GANT61 [46], HPIs 1–4 [45], and JK184 [47] that were previously identified from GLI-reporter cell-based screens. In a Hh functional cell based assay, C3H10T1/2, that we and others have used to assess the activity of Hh ligands and Hh inhibitors [52, 53], we found that these GLI antagonists showed varying effects at blocking canonical Hh signaling with JK184 being the most potent. JK184 was previously shown to reduce GLI1 mRNA expression in this cell-based assay [47].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A number of small molecules that act at the level of the GLI transcription factors have been identified with varying mechanisms and understanding of action and so we assembled a GLI antagonist panel consisting of GANT58 and GANT61 [46], HPIs 1–4 [45], and JK184 [47] that were previously identified from GLI-reporter cell-based screens. In a Hh functional cell based assay, C3H10T1/2, that we and others have used to assess the activity of Hh ligands and Hh inhibitors [52, 53], we found that these GLI antagonists showed varying effects at blocking canonical Hh signaling with JK184 being the most potent. JK184 was previously shown to reduce GLI1 mRNA expression in this cell-based assay [47].…”
Section: Discussionmentioning
confidence: 97%
“…The C3H10T1/2 assay was performed essentially as previously described [52, 53]. C3H10T1/2 cells were maintained in DMEM medium containing 10% FBS and plated in 96-well plates at 5000 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…The hybridoma expressing the anti-Shh 5E1 monoclonal antibody (mAb) originally developed by Thomas Jessell [1] , was obtained from the Developmental Studies Hybridoma Bank developed under the auspices of the NICHD and maintained by the University of Iowa, Department of Biology (Iowa City, IA, USA). The N-terminal domain of human Shh (ShhN, residues 24–197) was expressed and purified from E.coli essentially as previously described [2] , [3] , [4] . Thermo 384-well, flat-bottom, black, MaxiSorp plates (cat.…”
Section: Methods Detailsmentioning
confidence: 99%
“…We and others have previously demonstrated that Hh binds directly to heparin [2 , [4] , [5] , [6] . We have developed a 384-well automated solid-phase plate-based assay for identifying small molecule modulators of ShhN/heparin binding.…”
Section: Methods Detailsmentioning
confidence: 99%
“…Photoaffinity labeling (PAL) is a technique which uses a photoactivatable cross-linking group to induce covalent bonds to target proteins. , Benzophenone, one of the most commonly used cross-linking groups, forms a radical upon irradiation with light at 365 nm which is able to react with amino acids or nucleotides . It is widely used as a cross-linking group due to its selectivity, stability, and compatibility with many synthetic strategies and mild photoactivation conditions. , Incorporation of a benzophenone-containing unnatural amino acid into an engineered protein has previously been used to probe protein–protein interactions. This strategy, while effective, relies on the expression of the protein of interest at higher than physiological levels. To avoid exogenous protein overexpression, recent research has focused on the development of small molecule probes.…”
mentioning
confidence: 99%